1998
DOI: 10.1590/s0100-879x1998000100019
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic patterns associated with cure in human American cutaneous leishmaniasis

Abstract: Patients with American cutaneous leishmaniasis were studied before therapy (active lesion) and at the end of therapy (cured patients). Assays of lymphocyte proliferative responses of peripheral blood mononuclear cells induced in vitro by Leishmania braziliensis promastigote antigens (Lb) were performed. Antigen-stimulated cells were harvested for CD4 and CD8 phenotype analysis and the levels of gamma interferon (IFN-γ) and interleukin 4 (IL-4) produced were also determined in the culture supernatants. Two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
4
39
1
Order By: Relevance
“…Despite the small number of patients studied, we can speculate that the low percentage of apoptosis in CD8 + T cells of spontaneous healing patients may point to a significant role of this cell subpopulation in the mechanism of cure of LCL. This possibility is in accordance with previous results from our group (36)(37)(38)(39) showing that CD8 + T cells are associated with cure and protection in LCL.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the small number of patients studied, we can speculate that the low percentage of apoptosis in CD8 + T cells of spontaneous healing patients may point to a significant role of this cell subpopulation in the mechanism of cure of LCL. This possibility is in accordance with previous results from our group (36)(37)(38)(39) showing that CD8 + T cells are associated with cure and protection in LCL.…”
Section: Discussionsupporting
confidence: 93%
“…Our study focused primarily on the production of IFN-γ by these cells due to the involvement of this cytokine in resistance to and recovery from leishmanial infections (Carvalho et al 1995, Coutinho et al 1998, Ribeirode-Jesus et al 1998. When analyzing the production of this cytokine before treatment onset it was observed that cells from patients with chronic lesions produced more IFN-γ than those from patients with recent infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate the importance of the balance between T CD4 + and CD8 + cells, in which the first ones would have their proportion reduced during the healing process (10,11). Meanwhile, natural killer (NK) cells participate by secreting IFN-γ, important for the differentiation of Th1 and Th2 responses by CD4 + T cells, and also through direct cytotoxic effect on parasitized macrophages (12).…”
Section: Short Communicationmentioning
confidence: 99%